the evaluation of influencing factors of electronic customer relationship management adoption in e-commerce - Jalal Rezaeenour; Habil Deimazar (مدیریت مهندسی و رایانش نرم)
The concept of electronic customer relationship management (e-CRM) is among the most important subjects under discussion in academia and commercial environments. The decision on e-CRM adoption must be made based on different factors. These influential factors have different importance rates. In this paper, we studied the effects of factors for e-CRM adoption in e-commerce. To this end, we identified and examined the various factors that can be effective for implementing e-CRM in companies operating in the field of electronic commerce and proposed a conceptual model for the adoption of e-CRM by extracting some categories of effective components. Using three major components and a number of independent variables, this model evaluated their impact on the dependent variables' "adoption" as the target component. The conceptual model was presented for adoption using structural equation modeling (SEM). Furthermore, these factors were prioritized by fuzzy analytic network process (FANP) method. The consistency of the results obtained from these two different analytical techniques ensured that our results were valid and reliable.